Ethionamide Pharmacokinetics/Pharmacodynamics-derived Dose, the Role of MICs in Clinical Outcome, and the Resistance Arrow of Time in Multidrug-resistant Tuberculosis. (28th November 2018) - Deshpande, Devyani; Pasipanodya, Jotam G; Mpagama, Stellah G; Srivastava, Shashikant; Bendet, Paula; Koeuth, Thearith; Lee, Pooi S; Heysell, Scott K; Gumbo, Tawanda
Abstract: Background: Ethionamide is used to treat multidrug-resistant tuberculosis (MDR-TB). The antimicrobial pharmacokinetics/pharmacodynamics, the contribution of ethionamide to the multidrug regimen, and events that lead to acquired drug resistance (ADR) are unclear. Methods: We performed a multidose hollow fiber system model of tuberculosis (HFS-TB) study to identify the 0–24 hour area under the concentration-time curve (AUC0-24 ) to minimum inhibitory concentration (MIC) ratios that achieved maximal kill and ADR suppression, defined as target exposures. Ethionamide-resistant isolates underwent whole-genome and targeted Sanger sequencing. We utilized Monte Carlo experiments (MCEs) to identify ethionamide doses that would achieve the target exposures in 10000 patients with pulmonary tuberculosis. We also identified predictors of time-to-sputum conversion in Tanzanian patients on ethionamide- and levofloxacin-based regimens using multivariate adaptive regression splines (MARS). Results: An AUC0-24 /MIC >56.2 was identified as the target exposure in the HFS-TB. Early efflux pump induction to ethionamide monotherapy led to simultaneous ethambutol and isoniazid ADR, which abrogated microbial kill of an isoniazid-ethambutol-ethionamide regimen. Genome sequencing of isolates that arose during ethionamide monotherapy revealed mutations in both ethA and embA . In MCEs, 20 mg/kg/day achieved the AUC0-24 /MIC >56.2 in >95% of patients, provided the Sensititre assay MIC was <2.5 mg/L. In the clinic, MARS revealed that ethionamide Sensititre MIC had linear negative relationships with time-to-sputum conversion until an MIC of 2.5 mg/L, above which patients with MDR-TB failed combination therapy. Conclusions: Ethionamide is an important contributor to MDR-TB treatment regimens, at Sensititre MIC <2.5 mg/L. Suboptimal ethionamide exposures led to efflux pump-mediated ADR.